Nilai-Nilai Pendidikan Multikultural dalam al-Quran - Ahmad Izza Muttaqin (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
Pluralism is the uniqueness of a particular society or nation. Therefore it is expected from every society to accept pluralism as a grace which will nurture a healthy attitude, tolerance and mutual respect. Multicultural education aims to create a harmonious life in a multifaceted society. The values ​​of pluralism and diversity are not necessarily well received if not accompanied by collective awareness of various parties and the lack of participation from the education community. Education should play a role in resolving conflicts in the community. Education must be able to provide intelligent offers, among others, by designing materials, methods, and curricula that are able to awaken the community to the importance of mutual tolerance, respect for ethnic, religious, racial, ethnic and cultural differences between multicultural Indonesians. Al Quran in the letter Al hujurat: 13 expressly explains the values ​​of multicultural education that is: equality between men and women and respect differences among ethnic groups. In general, the above verse is understood as a description of the obligation to cooperate between men and women in various fields of life. multicultural education needs to be limited only to the issues of human civilization and human life between religious people who are not in conflict with the "decree" of Allah or aqidah.